PENGARUH FAKTOR DALAM DAN LUAR NEGERI TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) DI INDONESIA - Jul Fahmi Salim; Abd Jamal; Chenny Seftarita (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2017)
This study aims to analyze the effect of domestic (i.e. exchange rate and BIRATE) and foreign factor (i.e. KLSE, SET and global financial crisis) on the Jakarta Composite Index (JCI) in Indonesia. This research using secondary data in the form of quarterly from 2005: Q2 to 2016: Q2. This research using multiple regression analysis method. The result of this result show that KLSE and SET has positive and significant effect on JCI, and the exchange rate, BIRATE a significant has negative effect on JCI, while DKG has negative effect but not significant. Simultaneously there are influence betwen the exchange rate, BIRATE,KLSE, SET, and DKG of the JCI. Based on the results, the authors suggested that the government in this case Bank Indonesia to be careful in deciding the benchmark interest rate (BI Rate) and while maintaining exchange rate stability, so that JCI was able to show a positive trend.